Persuasive Communication RRI Pro 2 Padang in Improving Listening through Instagram Social Media - Ariyati, Yumi; Dwinto, Dwinto; Sumartono, Sumartono; Langita, Yasha (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
This study aims to determine persuasive communication RRI Pro 2 Padang in increasing listeners on Instagram social media and to find out the obstacles in carrying out persuasive communication and persuasive communication efforts carried out by RRI Pro 2 Padang in increasing listeners on Instagram social media. This study uses a qualitative method with a descriptive approach. The sampling technique used in this study used the Purposive Sampling technique, where the technique for taking samples of data sources is based on certain considerations, such as the person who knows best about what and the information we expect from the research. The research conducted uses the Theory Elaboration Likelihood Model (ELM) is a theory process double that explain change attitude a person. Theory This developed by Richard E. Petty and John Cacioppo in 1980. This theory is a general theory of attitude change which is believed to provide a fairly general framework for organizing, categorizing, and understanding the basic processes underlying effectiveness. communication persuasive. Persuasive communication conducted by RRI Pro 2, including using social media, can help RRI Pro 2 Padang in promoting their programs. To generate interest (desire) from listeners and watch or listen to programs presented by RRI Pro 2 Padang, it will require something that makes someone know about it and be interested. Persuasive communication is one of the most effective ways to do it, such as uploading content on Instagram to increase the number of listeners and followers of RRI Pro 2 Padang.